Repression of Escherichia coli purB is by a transcriptional roadblock mechanism. - He, B (1992)
Escherichia coli purB is regulated by a repressor-operator interaction. The purB operator is 242 bp downstream from the transcription start site and overlaps condons 62 to 67 in the protein-coding sequence (B. He, J. M. Smith, and H. Zalkin, J. Bacteriol. 174:130-136, 1992). The mechanism by which the repressor-operator interaction functions to repress transcription was investigated by a combination of promoter replacement experiments and RNA analyses. By using a trp promoter replacement that deleted 5' flanking DNA to position -986, purB expression was increased sevenfold, yet normal two- to threefold regulation was maintained. This indicates that repressor-operator control is independent of the purB promoter and other 5' flanking sequences. Transcriptional regulation was likewise independent of coupled translation. An approximately 260-nucleotide truncated in vivo purB mRNA was identified which was dependent upon repressor-operator interaction. Thus, binding of purine repressor to the purB operator inhibits transcription elongation by a roadblock mechanism. The roadblock was not influenced by a sevenfold increase in promoter strength or by an operator mutation resulting in a 2.5-fold increase in repressor-operator affinity.